Reformasi Kebijakan dan Pola Pikir Masyarakat Sebagai Upaya dalam Menegakkan Hak Asasi Manusia untuk Mencegah dan Menanggulangi Konflik Antar Agama - Surya Dharma Putra; Hery Firmansyah (CV Rewang Rencang, 2024)
The world is inhabited by people of various and diverse religious beliefs. Indonesia, in particular, embodies this diversity in terms of religion, ethnicity, and culture, which is manifested in the concept of Bhinneka Tunggal Ika (Unity in Diversity). However, this diversity also heightens the intensity of disputes and social conflicts among different elements of society, often resulting in discrimination and societal disintegration. One prevalent occurrence is inter-religious conflict, driven by differing perspectives and teachings, as well as religion-based discrimination, which causes both material and immaterial harm. This research employs a normative juridical method and relies on secondary data. The findings reveal that one of the consequences of such conflicts includes loss of life, destruction of places of worship, and the emergence of social stigma. Therefore, further study is necessary to assess the effectiveness and efficiency of legislation and government institutions or agencies related to the protection and enforcement of human rights.